How quotation and referential intentions modulate the derogatory force of slur utterances - Gray, David Miguel (Frontiers in Communication, 2024)
The need for new insights to understand the effects of quoting slurs in linguistic communication has been evident over the past several years. Slurs seem to be capable of offending even when embedded in quotations or mentioned. This ability of the derogatory force of slurs to project out of embeddings like quotations is an instance of what I will call the ‘projectible force’ of slurs. This force is taken to be a particularly serious problem for content-based semantic theories, which claim that what makes slurring utterances offensive is their derogatory content. The inert content criticism claims that quotations should render the content of a slur inert as quotations draw our attention only to the properties of the word itself. However, quoted or mentioned slurs can still offend, so the truth-conditional account of slurs must be wrong. I take the inert content criticism to be a locus of confusion. This confusion can be eliminated if we 1) disambiguate two notions of offense, 2) replace our naïve understanding of quotation with a more precise theory of quotation, and 3) use the deliverances of such a theory of quotation to help explain the different kinds of offense that can result from different features of slurring utterances. While this is not an attempt to defend the truth-conditional account of slurs, I will deliver something that both truth-conditional and prohibitionist accounts of slurs have failed to deliver: an explanation of how slurs under quotation can cause moral offense.